The effect of financial reporting quality on the dividend policies of companies listed in the Iraqi Stock Exchange - يحيى عباس حميد; حسين سطم صالح; حسين سطم صالح (Journal of Economics and Administrative Sciences, 2017)
Financial Reporting Quality (FRQ) is one of the important topics in the financial management, it has the impact on the users decisions, it also effect on many other variables i.e dividend, therefore. This paper aims to provide a diameter of Financial Reporting Quality (FRQ) level for the companies listed on the Iraqi Stock Exchange. It also tries to show the FRQ effects on the dividend policy. The study sample was 13 listed companies in the Iraqi Stock Exchange for the period from 2007 to 2011. Kothari et al. 2005 model has been used to measure the FRQ, on the other hand the common stock share of the dividend was used to measure the dividend. Many conclusions have been driven by the researcher, the most important of them are shown hereunder Accruals is an important measure in the earning quality approach, hence it enable the management to use the opportunity behavior because it can be manipulated easily. The dividend maximizes with increasing the financial reporting quality, hence the shareholders are fully aware about the company situation, that make the manipulation very difficult by the management. Based on the conclusions of present paper the researcher has recommended many of points, the most important of them are shown below: Its necessity to create a unit in the Iraqi Stock Exchange concerned with measuring the financial reporting for the listed companies, hence it helps to alarm the companies about the risk before occurred. It is a necessity for the Iraqi Stock Exchange and the company’s Board Of Directors (BOD) to give more importance to the dividend, because it effect on retained earnings (it is internal financing source that consider cheaper than the external sources), on the other hand it can affect the market value directly.